Monday

July 28, 2014

July 28, 2014

Posted by **Jesse Stone** on Friday, February 3, 2012 at 9:59am.

- Calculus -
**Steve**, Friday, February 3, 2012 at 11:52amf(x) = x^2 cos^-1(ln(sqrt(x))

f = uv, so f' = u'v + uv'

f' = 2x cos^-1(ln(sqrt(x)) + x^2 (cos^-1(ln(sqrt(x))'

Now, d/dx cos^1(u) = -1/sqrt(1-u^2) u'

u = ln(v), so u' = 1/v v'

v = sqrt(x), so v' = 1/2sqrt(x)

f' = 2x cos^-1(ln(sqrt(x)) + x^2 * -1/sqrt(1-ln^2(sqrt(x)) * 1/sqrt(x) * 1/2sqrt(x)

f' = 2x cos^-1(ln(sqrt(x)) - x/sqrt(4-ln^2(x))

**Related Questions**

math - cosA= 5/9 find cos1/2A are you familiar with the half-angle formulas? the...

Pre-Calculus - Find all solutions to the equation in the interval [0, 2pi) cos4x...

Calculus - If √2cos(x)-1 = (1+√3)/2 and √2cos(x)+1 = (1-√...

Calculus - find f'(x) if f(x)=x^2cos^-1(lnx)

calculus - If f(x)=2cos(4ln(x)) , find f'(x)

Vector Calculus - Hello...i had a question. I would really appreciate it if ...

trig - Find minimum value of 2cos x + 2cos y

trig - Find minimum value of 2cos x + 2cos y

trig - Find minimum value of 2cos x + 2cos y

Calculus - Find the area of the region enclosed between y = 2sin (x) and y = ...